Free and constrained sintering of 3-mol % yttria stabilised zirconia (2014)
Densification and shrinkage behaviour of ceramics or other powder materials can be predicted in a simple manner by using the master sintering curve. In this work, the densification data required to construct the master sintering curve of a 3-mol% yttria stabilised zirconia powder have been obtained. Bulk samples prepared by cold pressing, as well as thick films made of the same powder applied to a rigid substrate, were sintered. The free and constrained sintering experiments have been performed applying three different heating rates, with and without isothermal step at a maximum temperature of about 1450 °C. The shrinkage of the samples was measured in situ during densification using a push rod dilatometer. Also, a conventional box furnace was used, applying the same heating schedule, to compare the results. Microstructural analysis has been achieved by using scanning electron microscopy, environmental scanning electron microscopy, and optical microscopy. An acceptable agreement was obtained between similar samples sintered in the dilatometer and the box furnace, indicating that the dilatometer data could be used for both environments. The bulk samples reached lower densities than the films, probably due to their lower initial densities. For the samples free of constraint, a master sintering curve was achieved with an activation energy of 550 kJ mol-1. For the constrained case, problems associated with the substrate and the uncertainties in the measurements hindered the characterisation of the film, i.e., a single master sintering curve could not be produced.